Emergency Gastrectomy for Oesophageal and Gastric Polyps With Massive Bleeding Induced by Anticoagulation. Issue 4 (April 2023) - Ong, Chelsea T. W.; Palamuthusingam, Pranavan; Avramovic, John
We report the management dilemma of a patient with known gastric polyposis requiring anticoagulation for a submassive pulmonary embolism and haemodynamic compromise. This occurred in a comorbid patient with iron deficiency anaemia and previous venous thromboembolism. The patient had repeated episodes of gastrointestinal bleeding post-thrombolysis for which the cause was not seen on gastroscopy and required an emergency gastrectomy to control the bleeding. A keyword search was done across Scopus, PubMed, MEDLINE, and Embase; in the case of gastric polyposis causing significant bleeding, current practice is to identify and treat such cases with endoscopy. This case report delineates the first case in literature of haemorrhagic bleeding in gastric polyposis secondary to therapeutic anticoagulation which has gone on to require definitive surgical management.